2011
DOI: 10.1515/rns.2011.042
|View full text |Cite
|
Sign up to set email alerts
|

Translational research in transcranial direct current stimulation (tDCS): a systematic review of studies in animals

Abstract: Recent therapeutic human studies testing transcranial direct current stimulation (tDCS) has shown promising results, although many questions remain unanswered. Translational research with experimental animals is an appropriate framework for investigating its mechanisms of action that are still undetermined. Nevertheless, animal and human studies are often discordant. Our aim was to review tDCS animal studies, examining and comparing their main findings with human studies. We performed a systematic review in Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 56 publications
3
36
0
2
Order By: Relevance
“…Our findings make it difficult to assess the potential of using tDCS specifically for training subjects to use sensorimotor rhythm-based BCIs. However, such effects on cortical excitability could be of use for rehabilitation of neural disorders which exhibit significantly reduced or altered network synchronization in various frequency bands, such as stroke, paralysis, schizophrenia and depression [4], [8], [38]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings make it difficult to assess the potential of using tDCS specifically for training subjects to use sensorimotor rhythm-based BCIs. However, such effects on cortical excitability could be of use for rehabilitation of neural disorders which exhibit significantly reduced or altered network synchronization in various frequency bands, such as stroke, paralysis, schizophrenia and depression [4], [8], [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Behavioral studies have since revealed potential therapeutic applications of tDCS for a wide variety of disorders, including Parkinson’s, stroke, depression, schizophrenia, and addiction [3, 4, 8, 9]. EEG recordings following tDCS stimulation periods have revealed changes in resting state oscillatory neural activity, functional connectivity, and event related activity during cognitive tasks.…”
Section: Introductionmentioning
confidence: 99%
“…After the FORCEtraining with tDCS with the anode placed over M1, using a questionnaire developed by Brunoni et al (2011) andFertonani et al (2010), we asked participants to report the presence and severity (none-mild-moderate-considerable-strong) of feelings of itchiness, tingling, headache, neck pain, scalp pain, burning, warmth/heat, pinching, iron taste, fatigue, concentration difficulties and acute mood changes. In addition, the start (beginning, middle or end of stimulation) and duration (stopped soon, in the middle or towards the end of the stimulation) of these sensations was questioned and participants were asked if the sensations influenced their performance (not at all, a little, considerably, much, very much).…”
Section: Questionnairesmentioning
confidence: 99%
“…Experiments in animals (Bindman et al, 1964;Purpura and McMurtry, 1965;Brunoni et al, 2011) and humans (Nitsche and Paulus, 2000) have shown that the use of such currents induces polarity-specific effects that are not strictly restricted to the stimulated site (Stagg et al, 2009;Stagg and Nitsche, 2011;Polania et al, 2011aPolania et al, , 2011bKeeser et al, 2011;Pellicciari et al, 2013). These findings suggest that neuronal mechanisms underlying the described effects should involve synaptic strength changes and possibly the modulation of synaptic connectivity, leading to a viable way to induce changes in excitability (Stagg and Nitsche, 2011) and, therefore, the functionality of specific networks.…”
Section: Introductionmentioning
confidence: 99%